ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PTINDOFOOD SUKSES MAKMUR TBK DAN PT MAYORA INDAHTBK MENGGUNAKAN RASIO PROFITABILITAS, LIKUIDITAS,DAN AKTIVITAS PERIODE 2019-2023 - Dewi Khinasih (SUAN PUBLISHER, 2025)
This study aims to analyze and compare the financial performance of PT Indofood Sukses Makmur Tbk and PT Mayora Indah Tbk during the 2019-2023 period using profitability, liquidity, and activity ratios. The food and beverage industry was selected due to its significant contribution to the national economy and the increasingly intense competition in the era of globalization. The research employs a descriptive quantitative method using secondary data in the form of annual financial statements of both companies, obtained from the Indonesia Stock Exchange. The results show that PT Indofood Sukses Makmur Tbk generally demonstrated more stable financial performance and more aggressive growth in assets, sales, and profits. Meanwhile, PT Mayor Tbk performed superiorly in terms of Return on Assets (ROA) and Return on Equity (ROE). Indofood is also more efficient in utilizing assets and debt financing, while Mayora shows significant improvements in profit and operational efficiency at the end of the research period. This study contributes by comprehensively combining three key ratios, making it a valuable reference for company management and academics in decision-making and the development of financial performance analysis